New players in chronic lung disease identified at the European Respiratory Society International Congress in Paris 2018: from microRNAs to extracellular vesicles - Burgy, Olivier; Fernandez, Elena Fernandez; Enes, Sara Rolandsson; Königshoff, Melanie; Greene, Catherine M.; Bartel, Sabine (Journal of Thoracic Disease; Vol 10, Supplement 25 (September 2018): Journal of Thoracic Disease [Dedicated to the 28th International Congress of the European Respiratory Society (ERS 2018)], 2018)
Since the first description of microRNAs (miRNAs) in 1993 (1) a large and growing number of studies has explored their roles across a variety of biomedical research disciplines, including lung biology.